2020
DOI: 10.1080/00207233.2020.1802937
|View full text |Cite
|
Sign up to set email alerts
|

The effects of atmospheric stability with low wind speed and of air pollution on the accelerated transmission dynamics of COVID-19

Abstract: The goal of this study is to explain the relation among atmospheric stability/turbulence (considering wind speed), air pollution and the spread of COVID-19 to provide insights into environmental risk factors of specific regions. Results reveal that cities with high atmospheric stability, based on a low wind speed, and frequently high levels of air pollution-exceeding safe levels of ozone or particulate matter-had higher numbers of COVID-19 related infected individuals and deaths. This finding suggests that atm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
147
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 176 publications
(152 citation statements)
references
References 38 publications
2
147
1
2
Order By: Relevance
“…In fact, scholars state that a high level of air pollution can increase the viral infectivity and lethality of the COVID-19 [10]. In addition, atmosphere with low wind prevents the dispersion of air pollutants, which seem to be one of the determinants of higher incidence of COVID-19 in some European regions, such as North Italy [11]. The study by van Doremalen et al [12] revealed that in China, viral agents of SARS-CoV-2 may be suspended in the air for several minutes and this finding can explain higher number of cases and deaths related to COVID-19 in manifold countries, such as the USA, India, Brazil, Mexico, etc.…”
Section: Introduction and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, scholars state that a high level of air pollution can increase the viral infectivity and lethality of the COVID-19 [10]. In addition, atmosphere with low wind prevents the dispersion of air pollutants, which seem to be one of the determinants of higher incidence of COVID-19 in some European regions, such as North Italy [11]. The study by van Doremalen et al [12] revealed that in China, viral agents of SARS-CoV-2 may be suspended in the air for several minutes and this finding can explain higher number of cases and deaths related to COVID-19 in manifold countries, such as the USA, India, Brazil, Mexico, etc.…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…[13]. In general, several studies present the hypothesis that atmospheric pollution associated with certain climatological factors (such as, high humidity and low wind speed) may support a longer permanence of viral particles in the air, fostering the rapid spread of COVID-19 within polluted regions [5,11,12,14,15]. In this context, Martorell-Marugán et al [16] suggest new tools for supporting increased data analysis and statistical capabilities that allow users to explore trends and associations between critical environmental data and the spread of COVID-19 in society.…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…Hence, these conclusions are of course tentative because in the presence of the second and future waves of the COVID-19 pandemic manifold socioeconomic and environmental factors play a critical role (Coccia, 2020a(Coccia, , 2020b(Coccia, , 2020c(Coccia, , 2020d. There is need for much more detailed research on how COVID-19 pandemic and similar epidemics evolve in different economic, social, environmental and institutional contexts and especially in a specific period of time of a given geographical area (Coccia, 2020e).…”
Section: Resultsmentioning
confidence: 99%
“…Figures 1-2-3 show the trend of variables just mentioned confirming, ictu oculi, that the impact of the first wave of COVID-19 pandemic in Italy on public health has been stronger than second one in the first 105 days of the evolution of this pandemic. However, Figure 1 of confirmed cases reveals a growing trend for second pandemic wave, whereas the first one has a declining trend also because of lockdown and quarantine and the progression of COVID-19 pandemic towards summer season when the novel coronavirus seems to have a seasonality with natural reduction of transmission for better weather conditions (e.g., hot temperatures) and also low levels of air pollution for containment measures applied (cf., Coccia, , 2020aCoccia, , 2020bRosario Dentes et al, 2020). Figure 2 shows trends of admission to ICUs: the second wave has an intensity lower than first pandemic wave and both waves seem to have stable dynamics.…”
Section: Methods Of Statistical Analysismentioning
confidence: 99%
“…However, Figure 1 of confirmed cases reveals a growing trend for second pandemic wave, whereas the first one has a declining trend also because of lockdown and quarantine and the progression of COVID-19 pandemic towards summer season when the novel coronavirus seems to have a seasonality with natural reduction of transmission for better weather conditions (e.g., hot temperatures) and also low levels of air pollution for containment measures applied (cf., Coccia, 2020Coccia, , 2020aCoccia, , 2020bRosario Dentes et al, 2020 positive association of the coefficient of correlation is between fatality rates and confirmed cases (r=.24, pvalue <.05), whereas correlation between ICUs and confirmed cases is negative (r= −.22, p-value <.05). Table 2 seems to show that many infected individuals died as well as a lot of patients in ICUs likely because of low knowledge of the pathology and evolution of COVID-19 in patients, and lack of appropriate therapies and low number of ICUs in hospitals (Gattinoni et al, 2020;Sterpetti, 2020).…”
Section: Methods Of Statistical Analysismentioning
confidence: 99%